From corporate mess to corporate hygiene: dealing with corruption in Zimbabwe’s public sector. - Chilunjika, Alouis (Batalea Publishers, 2022)
Corruption has become so rampant and embedded in Zimbabwe that it has now become the scourge of our economic development agenda. Corruption can now be said to be the single most threat to our socio-economic development and progress. It has been noted that corruption has become so endemic in Zimbabwe that it is now viewed as an acceptable way of life at all levels of society. Corruption in Zimbabwe ranges from bribery, embezzlement of public funds or property, fraud, smuggling, externalization of funds, concealment of information, misuse or abuse of office or position for personal gain, extortion, misrepresentation, nepotism, tax evasion among others. Successfully dealing with corruption involves eliminating the opportunity for corruption by changing incentives, removing loopholes and getting rid of rules and regulations that encourage corrupt behaviour. An approach that focuses on changing the rules and the incentives, accompanied by appropriately harsh penalties for delinquent behaviour is likely to be far more effective if it is also supported by efforts to improve the moral and ethical behaviour of citizens among others can help to promote corporate hygiene. It is the thrust of this paper to unpack the strategies that are used in dealing with corruption in Zimbabwe’s public sector which then clears the corporate mess and foster corporate hygiene.